Racist call-outs and cancel culture on Twitter: The limitations of the platform's ability to define issues of social justice. (December 2020) - Bouvier, Gwen
Abstract: Studies point to the positive role Twitter can play in social justice campaigns. Using Critical Discourse Analysis, this paper looks in detail at one such case: a racist call-out in Canada, which trended on Twitter in many countries leading to its coverage in mainstream media outlets. It had the characteristics, labelled at the time by critics, of 'cancel culture', where there were calls for sackings and boycotts. This analysis demonstrates that there should be caution in regard to how social media platforms such as Twitter are able to lead in such matters of social justice. The paper shows how its affordances can work against coherent and careful discussion, fostering fast, simplified, contradictory commentary, where individual tweets load a range of different concerns onto a specific instance. In this particular case, this results in an individualization of racism, which therefore becomes decontextualized and depoliticized. While those tweeting revel in and enjoy their shared moral position, actual endemic structural racism in society remains invisible, and they misrepresent, arguably, the key question that this racist outburst raises.